Combustion processes in propulsion : control, noise and pulse detonation - Roy, G. D. (Elsevier Butterworth Heinemann, 2006)
Chemical propulsion comprises the science and technology of using chemical reactions of any kind to create thrust and thereby propel a vehicle or object to a desired acceleration and speed. This book focuses on recent advances in the design of very highly efficient, low-pollution-emitting propulsion systems, as well as advances in testing, diagnostics and analysis. It offers unique coverage of Pulse Detonation Engines, which add tremendous power to jet thrust by combining high pressure with ignition of the air/fuel mixture. Readers will learn about the advances in the reduction of jet noise and toxic fuel emissionssomething that is being heavily regulated by relevant government agencies. * Lead editor is one of the world's foremost combustion researchers, with contributions from some of the world's leading researchers in combustion engineering * Covers all major areas of chemical propulsion-from combustion measurement, analysis and simulation, to advanced control of combustion processes, to noise and emission control * Includes important information on advanced technologies for reducing jet engine noise and hazardous fuel combustion emissions.